Periprocedural warfarin reversal with prothrombin complex concentrate. Issue 139 (March 2016) - Sridharan, Meera; Wysokinski, Waldemar E.; Pruthi, Rajiv; Oyen, Lance; Freeman, William D.; Rabinstein, Alejandro A.; McBane, Robert D.
Abstract: Introduction: Approximately 10% of chronically anticoagulated patients require an invasive procedure annually. One in 10 procedures is emergent and requires prompt anticoagulation reversal. The study objective is to determine the safety and efficacy of a 3 factor prothrombin complex concentrate (PCC) for periprocedural anticoagulation reversal. Materials and Methods: Consecutive patients receiving 3 factor PCC for warfarin reversal for either urgent/emergent invasive procedures or major bleeding were analyzed. Primary endpoints included percent achieving INR < 1.5, peri-operative major hemorrhage, thromboembolism and death during the 40 day post-infusion period. Results: Between January 1, 2010–December 31, 2012, 52 patients were treated with PCC for pre-procedural warfarin reversal and 113 patients for major bleeding. Within the peri-procedure group, there were 24 intra-abdominal surgeries, 12 percutaneous interventions, 6 cardiothoracic surgeries, 5 orthopedic and 3 endoscopic procedures. INR values < 1.5 were achieved in 51% at 2.5 h post-infusion. Major bleeding (13%), thromboembolism (13%) and mortality rates (15%) were high. Within the major bleeding group, PCC therapy reversed INR values (< 1.5) in 75% of patients within 4 h. For this group, thromboembolism (21%) and mortality rates (16%) were likewise high. Post-PCC anticoagulation, reinitiated in 37%, had no impact on bleeding or thrombotic complications. Mortality rates were threefold higher for those patients not restarting warfarin therapy. Conclusions: Although PCC therapy promptly and effectively reverses INR values for patients requiring urgent/emergent invasive procedure both thromboembolic and fatal complications are soberingly high and call for judicious use of these agents in these high risk populations. Highlights: Each year, 10% of anticoagulated patients undergo an invasive procedure for which anticoagulation must be stopped. Prothrombin complex concentrates are the guideline endorsed agents for warfarin reversal. Over a 2 yr period, 166 patients received PCC at our institution (53 for emergent procedures and 113 for major bleeding). PCC therapy provided prompt INR reversal in both subsets of patients. Adverse event rates were high and call for judicious use of these agents.